2007
DOI: 10.1063/1.2709993
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin low temperature SiGe buffer for the growth of high quality Ge epilayer on Si(100) by ultrahigh vacuum chemical vapor deposition

Abstract: The authors report a method to grow high quality strain-relaxed Ge on a combination of low-temperature Ge seed layer on low temperature ultrathin Si0.8Ge0.2 buffer with thickness of 27.3nm by ultrahigh vacuum/chemical-vapor-deposition method without the need to use chemical mechanical polish or high temperature annealing. On 8in. Si wafer, the etch-pit density was 6×106cm−2. The root-mean-square surface roughnesses of Ge epitaxy by atomic force microscopy were 1.4 and 1.2nm for bulk Si and silicon-on-insulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 19 publications
4
43
0
Order By: Relevance
“…[10,13,14,18]). It is suggested that it is very difficult to fully relieve the strain in the Ge seed layer when growing at LT (300-400 1C).…”
Section: Article In Pressmentioning
confidence: 99%
See 3 more Smart Citations
“…[10,13,14,18]). It is suggested that it is very difficult to fully relieve the strain in the Ge seed layer when growing at LT (300-400 1C).…”
Section: Article In Pressmentioning
confidence: 99%
“…As that has been systemically investigated by Nakatsuru et al [13] and Loh et al [14], SiGe buffer layer is employed to provide LT Ge nucleation sites, coalesce and annihilate dislocations, and absorb partially strain energy from mismatch of Ge to Si. With the help of SiGe buffer layer, Ge films have much lower TDD values and no thermal annealing is required.…”
Section: Article In Pressmentioning
confidence: 99%
See 2 more Smart Citations
“…If we have an intermediate, partly relaxed layer [18][19][20] or a low-temperature seed layer with a large number of point defects [21][22][23], which was grown on the substrate prior to growing the main film, then such a layer will act as a source of threading dislocations, which will then penetrate into the next film layer as well. As soon as the film, as it grows on the preliminarily grown sublayer, reaches the thickness h c (601), favorable conditions for induced nucleation of complementary 601 MDs arise in the system; this then will lead to the formation of edge MDs at the interface between the film and the sublayer.…”
Section: Critical Film Thickness For Nucleation Of 901 Mdsmentioning
confidence: 99%